Insights for reducing the consumption of wildlife: The use of bear bile and gallbladder in Cambodia. Issue 4 (17th November 2020) - Davis, Elizabeth Oneita; Veríssimo, Diogo; Crudge, Brian; Lim, Thona; Roth, Vichet; Glikman, Jenny Anne
Abstract: Unsustainable wildlife use is one of the leading threats to earth's biodiversity. Historically, efforts to address this issue have been focused on increasing enforcement and anti‐poaching measures. However, recognition that such supply‐reduction measures may be inefficient has spurred a movement towards consumer research and behaviour change. Here, we used consumer research to investigate the consumption of bear bile and gallbladder in Cambodia. Our aim was to gather key consumer insights such as demographics, beliefs and the identification of trusted individuals and communication channels, which could be used to underpin future behaviour change efforts to reduce the consumption of bear bile and gallbladder. To accomplish this, we conducted 4, 512 structured quantitative interviews and 132 qualitative, semi‐structured interviews across Cambodia. We found that although the level of bear bile and gallbladder consumption varied across the country, consumers were largely homogenous in their beliefs and choice of trusted messengers. This indicates that behaviour change interventions grounded in these results may be effective in any of the eight areas surveyed. We believe our study strategy can be adapted and followed by other conservation organizations to ensure they are capturing essential information necessary for designing effective behaviour change campaigns. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. សេចក្តីសង្ខេប: ១. ការប្រើប្រាស់សត្វព្រៃដែលមិនមាននិរន្តរភាពគឺជាការគំរាមកំហែងឈានមុខជាងគេមួយទៅដល់ជីវៈចម្រុះរបស់ភពផែនដី។ កន្លងមក កិច្ចខិតខំប្រឹងប្រែងដើម្បីដោះស្រាយបញ្ហានេះត្រូវបានគេផ្តោតលើតែការបង្កើនការពង្រឹងការអនុវត្តច្បាប់និងវិធានការប្រឆាំងការប្រមាញ់។ ២. ទោះយ៉ាងណាក្តី ដោយមានការកត់សម្គាល់ថាវិធានការណ៍ដើម្បីកាត់បន្ថយការផ្គត់ផ្គង់តាមវិធីនេះប្រហែលជាមិនមានប្រសិទ្ធភាព ដែលជាហេតុជំរុញឱ្យមានចលនាឆ្ពោះទៅរកការសិក្សាស្រាវជ្រាវអំពីអ្នកប្រើប្រាស់និងការផ្លាស់ប្តូរឥរិយាបទពួកគេ។ នៅទីនេះយើងបានប្រើវីធីសាស្រ្តសិក្សាស្រាវជ្រាវដើម្បីស៊ើបអង្កេតទៅលើការប្រើប្រាស់ទឹកប្រមាត់និងប្រមាត់ខ្លាឃ្មុំនៅប្រទេសកម្ពុជា។ ៣. គោលបំណងរបស់យើងគឺដើម្បីប្រមូលការស្វែងយល់សំខាន់ៗអំពីអ្នកប្រើប្រាស់ដូចជា ព័ត៌មានប្រជាសាស្ត្រ ជំនឿ និងការកំណត់អត្តសញ្ញាណបុគ្គលដែលពួកគេទុកចិត្តនិងបណ្តាញទំនាក់ទំនងផ្សេងៗ ដែលអាចត្រូវបានប្រើប្រាស់ដើម្បីគាំទ្រដល់ការអនុវត្តការផ្លាស់ប្តូរឥរិយាបទនាពេលអនាគត ដើម្បីកាត់បន្ថយការប្រើប្រាស់ទឹកប្រមាត់និងប្រមាត់ខ្លាឃ្មុំ។ ដើម្បីសំរេចគោលដៅនេះយើងបានប្រើប្រាស់វិធីសាស្ត្រសំភាសន៍តាមបែបបរិមាណវិស័យចំនួន ៤, ៥១២ នាក់ និងតាមបែបគុណវិស័យចំនួន ១៣២នាក់ (Semi‐structured Interviews) នៅទូទាំងប្រទេសកម្ពុជា។ ៤. ទោះបីយើងបានរកឃើញថាកម្រិតនៃការប្រើប្រាស់ទឹកប្រមាត់និងប្រមាត់ខ្លាឃ្មុំមានភាពខុសប្លែកគ្នានៅទូទាំងប្រទេសក៏ដោយ ក៏អ្នកប្រើប្រាស់ភាគច្រើនមានភាពដូចគ្នានៅក្នុងជំនឿនិងអ្នកដែលមានឥទ្ធិពលទៅលើពួកគេ។ នេះបង្ហាញថាអន្តរាគមន៍នៃការផ្លាស់ប្តូឥរិយាបទដែលមានមូលដ្ឋានបានពីលទ្ធផលទាំងនេះអាចមានប្រសិទ្ធិភាពនៅក្នុងតំបន់ណាមួយក្នុងចំណោមតំបន់ទាំងប្រាំបីដែលបានធ្វើការស្ទង់មតិ។ ៥. យើងជឿជាក់ថាយុទ្ធសាស្ត្រសិក្សារបស់យើងអាចត្រូវបានកែសម្រួលនិងអនុវត្តតាមអង្គការអភិរក្សដទៃទៀត ដើម្បីធានាថាពួកគេកំពុងចាប់យកព័ត៌មានសំខាន់ៗដែលចាំបាច់សម្រាប់ការរៀបចំយុទ្ធនាការផ្លាស់ប្តូរឥរិយាបទដែលប្រកបដោយប្រសិទ្ធភាព។